Dual Antiplatelet and Glycoprotein Inhibitors in Emergency PCI - Ling, Hwei Sung; Alan, F.Y.Y. (Singapore Springer, 2018)
Platelet inhibition remains the core pharmacotherapy component in patients under-going emergency or primary percutaneous coronary interventions (PCI). This can be achieved using a number of intravenous and oral preparations. Intravenous (iv) antiplatelets include various glycoprotein IIb/IIIa (GPIIb/IIIa) inhibitors and the only available intravenous P2Y12 inhibitor, cangrelor. Available oral agents include aspirin and various P2Y12 inhibitors or their analogues. These are usually used in combination with the intention to maintain dual antiplatelet therapy (DAPT) for a period of time (generally up to 12 months) after the index PCI procedure.Understanding and appropriate use of antiplatelet agents are vital in optimizing clinical outcomes of patients with acute coronary syndromes, particularly in the emergency setting where the patient may be naïve to all pharmacological agents. In this review, an overview on antiplatelet therapy for patient needing emergency PCI is described, including evidence from important clinical trials and suggested anti-platelet therapy regimens by published clinical practice guidelines.